Developmental authenticity - underlying dynamics of inner work processes - Liesenfeld, Kerstin M.; Lebedinski, Sabine; Parks, Anna Katharina; Dammann, Olaf (Frontiers in Psychology, 2024)
An emerging body of research attends to grasp the concept of authenticity. Nonetheless, a view on the developmental part with its underlying facets of Inner Work processes, is rare. In this paper, we aim to take a deeper look into the dynamics of inner work processes, that define certain authenticity developmental stages. Building upon our recently proposed "4Cview" of authenticity, we approach this developmental perspective from two different angles: from a process characteristic angle and a developmental level angle. Using vignettes of authentic client personality coaching processes, we propose that the interwoven dynamic between those two aspects yields several combinations of maturity levels within the individual. Continuity as an overarching concept thus contains various developmental authenticity stages that could be identified through different markers and vary in particular contexts.